Profit and chemical analysis of Lavandula dentata L. and Rosmarinus officinalis L. essential oils and the influence of factors stressors (Acta Scientiarum. Biological Sciences, 2024)
The anatomical, physiological, and environmental changes of plants can alter the production of essential oil. The present study aims to characterize the profit and chemical constituents of Lavandula dentata L and Rosmarinus officinalis L. essential oils (EO), grown under conditions of stress by solar, water and soil radiation. A completely randomized design (CRD) was used in triplicate. The biomass analysis showed that in both plants, the best results were obtained when it was subjected to lighting, shading and 100% fertilization, but there was the lowest profit of EO. The portion that had the lowest biomass, showed the highest profit of EO. In the EO of Lavandula dentata L there were as major compounds: nerol, linalol and Myrcene, respectively, as the product with the lowest profit, eucalyptol stood out, followed by camphor and fenchone. The EO of Rosmarinus officinalis L with the lowest profit showed alpha-pinene as the major constituent, followed by camphor, 1.8 cineol, alpha-Terpinolene and linalol, and the EO with the highest profit was caryophyllene. The constituents of the EO showed different results when comparing the products obtained from the highest and lowest profit, both qualitatively and quantitatively, which shows that plants under different stress conditions affect the production of these secondary compounds, which may indicate differences in pharmacological actions.